2020
DOI: 10.3389/fphy.2020.00280
|View full text |Cite
|
Sign up to set email alerts
|

A Correlation Between Solutions of Uncertain Fractional Forward Difference Equations and Their Paths

Abstract: We consider the comparison theorems for the fractional forward h-difference equations in the context of discrete fractional calculus. Moreover, we consider the existence and uniqueness theorem for the uncertain fractional forward h-difference equations. After that the relations between the solutions for the uncertain fractional forward h-difference equations with symmetrical uncertain variables and their α-paths are established and verified using the comparison theorems and existence and uniqueness theorem. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In [14,15], the authors introduced the discrete fractional sums and differences which produced directly from the Riemann-Liouville (RL) fractional integrals and derivatives, respectively. To review the history of discrete fractional operators, their properties and information related to discrete fractional calculus applications one can refer to [16][17][18][19][20][21][22] and the references therein. Nowadays, being new fractional integral and derivative operators make the researchers attempt to introduce a new definition of discrete fractional sum and difference operators corresponding to them.…”
Section: Introductionmentioning
confidence: 99%
“…In [14,15], the authors introduced the discrete fractional sums and differences which produced directly from the Riemann-Liouville (RL) fractional integrals and derivatives, respectively. To review the history of discrete fractional operators, their properties and information related to discrete fractional calculus applications one can refer to [16][17][18][19][20][21][22] and the references therein. Nowadays, being new fractional integral and derivative operators make the researchers attempt to introduce a new definition of discrete fractional sum and difference operators corresponding to them.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, researchers introduced various models involving fractional derivative and integral operators of arbitrary order (see [10]). Some recent contributions to the theory of fractional differential (or difference) equations and its applications can be found in [11][12][13][14][15][16][17] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DFC has been suitably characterized the term "memory" especially in physics, economics, mathematics, biology, engineering, control etc., and its study is not only interesting from a purely mathematical point of view, but has been found extremely useful for modeling super-diffusion processes, which naturally appear in many applications in biology, probability, physics, economics, medicine and ecology (see [1][2][3][4]). Additionally, there are some recent works on variable-order fractional difference equations such as [5][6][7][8][9][10] in discrete fractional calculus.…”
Section: Introductionmentioning
confidence: 99%